A Review: Potential of Waste Materials in Tiles Production - Hamid, Nor Baizura; Mohammad Azm, Mohamad Azim; Abdullah, Noorul Hudai; Mokhtar, Mardiha; Prasetijo, Joewono; Che Muni, Muhammad Fahmi; Zainudin, Muhammad Haziq Fahmi; Abu Bakar, Adib Irfan Naqiuddin (Multidisciplinary Applied Research and Innovation, 2020)
The floor is one of the important elements in a building. It should provide a flat surface to the building. Usually, in the construction industry, floor surfaces made of concrete are often used. This is because, concrete floors are stronger, more durable, and economical. Although concrete floors have many advantages, they still have a disadvantage which is a less attractive surface. Besides, the use of existing tiles found on the floor and walls often poses a danger to the user if the tile cracks or breaks. Therefore, floor finishing is essential to overcome this disadvantage. The floor finishes can highlight the beauty and can provide comfort for the users of a building. Among the finishes that are often used in industry is tile. This finish can be used on the floor as well as the walls as an outer layer to produce light tiles, low water absorption percentage, and durable. To overcome this problem, this study was conducted to analyze the use of waste materials as materials replacement in tile making. By finding sources from articles and journals using a four-stage process namely identification, inspection, qualification, and included to identify the physical and mechanical properties of the material based on seven types of testing that have been done namely combustion shrinkage, water absorption, Density, porosity, tensile strength, and compression. The results show that an electric arc furnace (EAF) has a high value for firing shrinkage tests, so this indicates that EAF has a low indicator of flammability compared to other materials. For the water absorption test, the lowest water absorption percentage value for tile manufacturing using substitute material is EAF, with a lower water absorption rate which is from 0.5% to 0.15%. overall, based on standard testing of EAF, the results show that EAF can meet the standards that have been set to produce tiles. Among the standard features of tiles that can be achieved by EAF are from the firing shrinkage, density, and water absorption.